Friction losses in valves and fittings for liquid food products - Cabral, R. A. F. [UNESP]; Telis, V. R. N. [UNESP]; Park, K. J.; Telis-Romero, J. [UNESP] (Inst Chemical Engineers, 2011)
Data on pressure drop were obtained in stainless steel, sanitary fittings and valves during laminar and turbulent flow of egg yolk, coffee extract, blackberry juice and concentrated milk, which were selected as typical liquid food products. The rheological properties of these fluids were obtained from previously published studies and the power-law model provided the best description of the rheological behavior of these liquids. Friction losses were measured in fully and partially open butterfly, seat, no-return and ball valves, bends, tees and unions. Values of loss coefficients (k(f)) were calculated and correlated as a function of the generalized Reynolds number by the two-k method. The model adjustment was satisfactory, being better in the laminar flow range (0.884 <= r(2) <= 0.999) than in the turbulent one (0.751 <= r(2) <= 0.989). In order to test the adequacy of the results that are needed to predict loss coefficients during flow of liquid food products, measurements were carried out during the flow of orange juice in the same temperature range at which the correlations were obtained. The flow of coffee extract and egg yolk at different temperatures than those of the correlations were also analyzed. Comparison between experimental and predicted loss coefficients showed very good agreement. (C) 2010 The Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: Pressure drop; Non-Newtonian liquids; Friction factor; Loss coefficients